Inhibitor of biological effects of interleukin-6 sarilumab in treatment of rheumatoid arthritis - D. E. Karateev; E. L. Luchikhina (Медицинский совет, 2019)
Despite progress in pharmacotherapy, there still are urgent needs in the development of new methods of drug therapy of rheumatoid arthritis (RA). New prospects for drug therapy are currently associated with sarilumab (SAR), recently registered in the Russian Federation for the treatment of moderate to highly active RA in adult patients. SAR binds to both membrane and soluble interleukin-6 receptors (IL-6r), blocking its pro-inflammatory effect. SAR has certain differences from its predecessor, tocilizumab: it is a fully human, not humanized, antibody, it is injected subcutaneously once every 2 weeks, it has a more pronounced affinity for IL-6r. SAR is a highly effective treatment for patients with RA, it has shown higher efficacy in monotherapy compared to the representative of the class of TNF inhibitors adalimumab. Clinical studies have shown approximately equal clinical efficacy parameters and a safety profile for SAR and tocilizumab. Sarilumab should be considered as a first-line biologic drug in patients with high inflammatory activity, as well as in patients resistant to anti-TNF.